Changes In Profit For Idx-Listed Cigarette Companies Between 2018 And 2021 And Their Relative Importance To Net Profit Margin, Roe, And Roa - Danna Solihin; Andi Indrawati Indrawati; Nurfitriani; Muhammad Nur (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study aims determine and analyse the impact of Net Profit Margin, Return On Equity, and Return On Assets on the profit changes of BEI-listed tobacco companies from 2018 to 2022. Multiple linear regression analysis, the normality test, the autocorrelation test, the multicollinearity test, the heteroscedasticity test, the coefficient test, and the t test are employed as analytic instruments. According to research, Net Profit Margin (NPM) has a significant impact on the Changes in Profits of Cigarette Companies on the IDX in 2018-2021, while Return On Assets (ROA) and Return On Equity (ROE) do not. Net Profit Margin (NPM) has a significant impact on changes in profit; when NPM is high, a company is able to generate high profits from each transaction and/or reduce costs, ensuring that profit growth will continue to increase. Return On Assets (ROA) and Return On Equity (ROE) have no significant effect on changes in company profits because the increase in Return On Assets (ROA) and Return On Equity (ROE) is not only caused by increased profits generated by the company, but can also be caused by a decrease in the total assets or equity of the company even though the profits generated tend to remain in the same period, so that under these conditions the ratio of profits to total assets and equities tends to remain constant.